Recurrence Relation and Accurate Value on Inverse Moment of Discrete Distributions. (5th July 2015) - Wang, ChunYuan; Wuyungaowa,
Abstract : Properties of the generalized hypergeometric series functions are employed to get the recurrence relation for inverse moments and inverse factorial moments of some discrete distributions. Meanwhile, with the existence of the recurrence relations, the accurate value for inverse moment of discrete distributions can thus be obtained.